Influence of Big Five Personality Traits on Self-Disclosure in Early Adulthood Instagram Social Media Users - Ahmad Muflih; Kurniati Zainuddin; Muhrajan Piara (PT ARRUS Intelektual Indonesia, 2024)
Self-disclosure is the ability of individuals to voluntarily disclose information about themselves to others that is personal. This will affect both him and others, if done excessively. From the influence of self-disclosure factors based on personality type can be seen and focus on the personality of the big five personality in Makassar State University students. This study involved students of Makassar State University (N=381). The sampling technique used is cluster random sampling. The measuring instruments used are the Big Five Inventory scale (BFI) adaptation scale from Ramdhani (2012) and the self-disclosure scale from Tamaraya research (2020). Data analysis used in this study is a multiple linear regression technique. The results showed that there is not significant influence with the four big five personality, namely, Openess to experience, conscientiousness, extraversion, and agreeableness to self-disclosure. While personality neuroticism has a significant effect on self-disclosure. This research has implications in the field of Social Psychology and is useful for students to be able to determine the value of attitudes, emotions, and values that affect individuals on personality that are carried out towards self-disclosure.